Authoritarian Regime Learning: Comparative Insights from the Arab Uprisings - André Bank; Mirjam Edel (German Institute of Global and Area Studies (GIGA), 2015)
This paper examines the learning of authoritarian regimes in the early phase of the Arab uprisings. Differentiating conceptually between learning and policy change, we analyze and compare the authoritarian regimes of Algeria, Bahrain, Jordan, and Syria and their reactions to the challenge of "late riser" oppositional protests. We first show that the four regimes initiated very diverse measures in the domains of repression, material co-optation, and legal reforms. With regard to the sources of learning, we find that proximity is a determining factor, in terms of both geography and political similarity. Using the case of Bahrain, we then demonstrate that structural factors such as internal power structures, regional and international pressures, or state capacity can decisively constrain the implementation of learning-induced policy change. Overall, the paper aims to contribute to the emerging research on the international dimension of authoritarian regimes in the Middle East and beyond.
Keywords: 300; learning; authoritarian regimes; Arab Spring; policy change; lesson-drawing